Initiation factor 2, tRNA, and 50S subunits cooperatively stabilize mRNAs on the ribosome during initiation - Masuda, Tomoaki (National Academy of Sciences, 2012)
Initiation factor 2 (IF2) is a key factor in initiation of bacterial protein synthesis. It recruits initiator tRNA to the small ribosomal subunit and facilitates joining of the large ribosomal subunit. Using reconstituted translation system of Escherichia coli and optical tweezers, we directly measure the rupture force between single ribosomal complexes and mRNAs for initiation complexes in the presence and the absence of IF2. We demonstrate that IF2 together with codon recognition by initiator tRNA increases the force required to dislocate mRNA from the ribosome complexes; mRNA stabilization by IF2 required the presence of a joined 50S subunit, and was independent of bound guanine nucleotide. IF2 thus helps lock the 70S ribosome over the start codon during initiation, thus maintaining reading frame. Our results show how mRNA is progressively stabilized on the ribosome through distinct steps of initiation.